Evaluation of the Implementation of the Pancasila Student Profile Strengthening Program in Indonesian Junior High Schools Using the CIPP Model - Mastur; Bunyamin Maftuh; Sarbaini; Encep Syarief Nurdin; Raisa Aditya Putri (Universitas Veteran Bangun Nusantara, 2025)
Educational transformation in Indonesia emphasizes strengthening the character of students through the Pancasila Student Profile Strengthening Project (P5) as part of the implementation of the Merdeka Curriculum. This study aims to evaluate the implementation of the P5 program with the theme of “Entrepreneurship” in Banjarbaru City Junior High Schools using the CIPP (Context, Input, Process, Product) evaluation model. This study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects include school principals, teachers, facilitators, and seventh and eighth-grade students as program implementers. The results of the study indicate that the program was successfully implemented with an overall effectiveness rate of 90%. These results confirm that the program was implemented very well, starting from the selection of the theme based on the need to improve students' creative dimensions and their high interest in entrepreneurship. In terms of inputs, infrastructure, human resources, and funding were optimally fulfilled. The implementation process proceeded systematically through four stages—introduction, contextualization, action, and reflection—although student participation only reached 80% due to the perception that the program was separate from formal learning. Product evaluation showed students' success in creating creative products and an increased interest in continuing entrepreneurial activities independently. In conclusion, the implementation of the P5 program with an entrepreneurship theme in junior high schools is considered effective in fostering students' creativity, independence, and managerial skills. The CIPP evaluation model has proven to provide a comprehensive overview of the program's strengths and challenges and serves as the basis for recommendations to increase student participation, strengthen collaboration between teachers and parents, and maintain the sustainability of Pancasila values in learning.